Apical-basal polarity proteins are required cell-type specifically to direct photoreceptor morphogenesis - Hwa, Jennifer J. (2012)
Insect photoreceptor function is dependent on precise placement of the rhabdomeres, elaborated apical domains specialized for capturing light, within each facet of a compound eye [1]. In Diptera, an asymmetric arrangement of rhabdomeres, combined with a particular pattern of axonal connections, enhances light sensitivity through the principle of neural superposition [2–3]. To achieve the necessary retinal geometry, different photoreceptors (R cells) have distinct shapes. The Crumbs and Bazooka complexes play critical roles in directing rhabdomere development [4–9], but whether they might direct cell-type specific apical architectures is unknown. We demonstrate that while mutations in Bazooka complex members cause pleiotropic morphogenesis defects in all R cell sub-types, Crumbs (Crb) and Stardust (Sdt) function cell-autonomously to direct early stages in rhabdomere assembly in specific subsets of R cells. This requirement is reflected in the cell-type specific expression of Crb protein, and demonstrates that Sdt and Crb can act independently to similar effect. These two genes are also required for zonula adherens (ZA) assembly, but display an unusual pattern of cellular redundancy for this function, as each gene is required in only one of two adjoining cells. Thus our results provide a direct link between fate specification and morphogenetic patterning, and suggest a model for ZA assembly.